دراسة تاريخية تحليلية لتحديث خانات محور سوق الصاغة-البزورية في مدينة دمشق القديمة خلال القرن الثامن عشر - عرقاوي عبير (Latakia University Journal -Engineering Sciences Series, 2014)
يبين البحث الأهمية التاريخية لخانات محور سوق الصاغة البزورية الذي يقع في مركز مدينة دمشق القديمة إلى الجهة الجنوبية من الجامع الاموي في دمشق التي كانت تعد من أهم المدن التجارية الإسلامية في القرن الثامن عشر. ويبلغ عدد الخانات التي تشملها الدراسة 7 خانات من أصل 16 خاناً تقع في المدينة القديمة، وهي تعود بمعظمها للفترة العثمانية وتقع في المحور المدروس. يتعرض البحث للخانات التالية: خان الرز، خان العمود، خان الصنوبر، خان الصدراني، خان السفرجلاني، خان سليمان باشا وخان اسعد باشا. و يحدد من خلال الدراسة المقارنة العناصر المشتركة والمتغيرة (تصميم وإنشاء) المرتبطة بالفترة الزمنية للبحث وذلك قبلَ القرن الثامن عشر و أثناءَه. والتي تبين ظهور نظام التغطية الجديد للخانات المدروسة، وذلك بعرض لمخططات إعادة التصور وإظهار التحديث الذي تم خلال القرن الثامن عشر ، حيث اعتمدت الخانات النظام الجديد (موضة العصر التقبيب) مثال خان اسعد باشا والرز، أو التجديد على الخانات القائمة مثال خان العمود الذي كان شاهداً على هذا التحول من خان له صحن مكشوف واحد إلى صحنين مقببين. سيظهر البحث أهمية محور الصاغة البزورية بما يضمه من خانات كجزء مهم من التنظيم العمراني للمدينة، بالإضافة إلى تحديث الاقتصادي والتجاري الذي ارتبط ارتباطاً وثيقاً بتاريخ إحياء المدينة وتجديدها. The Research focuses on the historic value of Souq Al-Sagha al-Bzourya, which has a central location in the old city of Damascus,to the south of the Umayyad mosque. During the Ottoman period, Damascus was one of the most important provincials’ cities, the commiercial remained an important function, as witnessed by a number of Khans. The old city has 16 khans related to the ottoman period, 7 of them in the studied market. The study compares between the historic Khans and defines their Changes(design and construction) ,what are the similar and different elements and when they have been built; Additions and Changes. The studied Khans are: Khan Assad Bacha, Khan al- Ruz, Khan al- Amoud, Khan al- Sanouber, Khan al- Tutun, Khan al- Sudrani, and Khan al- Saferjalani. The Changes of the constructions before and after the 18th century were a witness of, the modernizing of the khans ,which give an additional view of the new development of the planning of the Market (souqe) Al –Sagha Al- Bzourya and its khans, and Khan al-Amoud is an example of this changes, from a design with an open courtyard to the covered hall. The studied market (souq) was a part of the city planning and the modernizing of the caravansaries(khans) were a part of the economic and commercial development of the city and its rehabilitation.